(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
In the context of modernizing higher music education in Kazakhstan, returning to oral tradition as a living source of artistic and pedagogical experience is particularly relevant. In this regard, the folk genre Qara olen serves as an effective tool for developing creativity, musical thinking, and communication skills in the younger generation. Within the system of higher music education, the ethno-solfeggio course focuses on the cultural and historical reproduction of traditional musical art. It is a comprehensive discipline where the theoretical foundations of traditional Kazakh song are integrated into a broad cultural and historical context. Through interactive methods, oral, and creative forms of work based on improvisation and creative interpretation of song folklore, students not only master the musical and poetic structure of the Qara olen genre but also immerse themselves in the socio-cultural context of traditional Kazakh music. Research indicates that the integration of the Qara olen folk genre into the educational process contributes to the revival and formation of national identity, enhances learning motivation, and promotes the development of artistic self-realization in the younger generation.